2022
DOI: 10.1101/2022.10.12.511771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The kleisin subunit controls the function of meiotic cohesins by determining the mode of DNA binding and differential regulation by SCC-2 and WAPL-1

Abstract: The cohesin complex plays essential roles in chromosome segregation, 3D genome organisation, and DNA damage repair through its ability to modify DNA topology. In higher eukaryotes, meiotic chromosome function, and therefore fertility, requires cohesin complexes containing meiosis-specific kleisin subunits: REC8 and RAD21L in mammals and REC-8 and COH-3/4 in C. elegans. How these complexes perform the multiple functions of cohesin during meiosis and whether this involves different modes of DNA binding or dynami… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Recently, it is shown that a DDR kinase, ATM, regulates cohesin association through the inactivation of WAPL in early prophase I in C. elegans meiosis (Z. Yu et al, 2023). And also, in C. elegans , two meiosis‐specific cohesin with REC‐8 or COH‐3/4 display distinct dynamics on the meiotic chromosome (Castellano‐Pozo et al, 2023). While REC‐8 cohesin stably binds to the chromosome, COH‐3/4 cohesin is dynamic with the association and dissociation in meiotic prophase I.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it is shown that a DDR kinase, ATM, regulates cohesin association through the inactivation of WAPL in early prophase I in C. elegans meiosis (Z. Yu et al, 2023). And also, in C. elegans , two meiosis‐specific cohesin with REC‐8 or COH‐3/4 display distinct dynamics on the meiotic chromosome (Castellano‐Pozo et al, 2023). While REC‐8 cohesin stably binds to the chromosome, COH‐3/4 cohesin is dynamic with the association and dissociation in meiotic prophase I.…”
Section: Discussionmentioning
confidence: 99%
“…Images were acquired on a Delta vision microscope as 3D stacks using the same exposure settings between genotypes to be compared. Quantitative analysis of fluorescence intensity was performed as previously described 62 . Briefly, non-deconvolved images were analysed in Image J using a customized macro.…”
Section: Quantification Of Fluorescence Signal Intensities To Measure...mentioning
confidence: 99%